Methods of wintering steer calves that are to be grazed a full season and sold off grass. - Smith, E.F.; Good, D.L.; Cox, R.F. (Kansas Agricultural Experiment Station, 2012)
This is a report on the wintering phase of this test. It will be completed at the close of the grazing season in 1952. This study is to determine the best method of wintering good quality steer calves that are to be grazed on bluestem pastures the following summer and sold off grass.
Keywords: Beef; Wintering methods; Bluestem pasture; Gain